High-Quality Genome Assembly of Chrysaora quinquecirrha Provides Insights Into the Adaptive Evolution of Jellyfish - Xia, Wangxiao; Li, Haorong; Cheng, Wenmin; Li, Honghui; Mi, Yajing; Gou, Xingchun; Liu, Yaowen (Frontiers in Genetics, 2020)
Jellyfish, such as Chrysaora quinquecirrha, hold an important evolutionary position and have great ecological value. However, limited genomic resources are currently available for studying their basic genetic and development processes. Here, we de novo assembled the first high-quality reference genome of C. quinquecirrha, and successfully annotated 21,606 protein-coding genes. Codon usage analysis identified the frequent use of low-GC-content codons during protein-coding gene translation. Analysis of the relative evolution rate indicated that jellyfish had a faster evolution rate than sea anemones but slower rate than the species in Hydrozoa. Phylogenetic analysis with two other species of jellyfish indicated that Aurelia aurita and Nemopilema nomurai have a closer relationship with each other than with C. quinquecirrha, with divergence from their common ancestor occurring approximately 475.7 million years ago. Furthermore, comparative genomics analysis identified that the biological signal pathways were specifically enriched in all three jellyfish genomes, suggesting these genes may have great contributions in the unique development and adaptive evolution process of jellyfishes. Our study not only showed the genomic characteristics and molecular adaptive evolution of C. quinquecirrha, but also provides valuable genomic resources for further study on complex developmental processes and environmental adaptations.